A prospective clinical trial comparing Biobrane® Dressilk® and PolyMem® dressings on partial-thickness skin graft donor sites. Issue 2 (March 2016) - Schulz, Alexandra; Depner, Christian; Lefering, Rolf; Kricheldorff, Julian; Kästner, Sonja; Fuchs, Paul Christian; Demir, Erhan
Highlights: Dressilk ® and Biobrane ® superior in wound assessment, inflammation, exudation. All three dressings were equivalent for epithelialization, pain, acute bleeding. PolyMem ® and Dressilk ® were superior to Biobrane ® in cost efficiency. High satisfaction rates with Dressilk ® and Biobrane ® regarding comfort and mobility. Abstract: Introduction: In a single-center, prospective, randomized clinical trial three different configured wound dressings Biobrane ®, Dressilk ® and PolyMem ® were compared with each other regarding objective and subjective healing parameters and cost efficiency. Methods: 28 burn patients received surgical treatment with split-thickness skin grafting, while utilizing Biobrane ®, Dressilk ® and PolyMem ® as a single bound donor site wound dressing in all patients. Following a standardized case report form, we monitored several parameters such as pain, transparency of the dressing, active bleeding, exudation and inflammation by using the Verbal Rating Scale 1–10 through out. Results: With regard to re-epithelialization, pain and acute bleeding all three dressings were equivalent. Dressilk ® and Biobrane ® presented clearly superior to PolyMem ® in both wound assessment and in the reduction of mild inflammation and exudation. High subjective satisfaction rates were reported with Dressilk ® and Biobrane ® dressings in regard to comfort and mobility. During the continuous monitoring period Biobrane ® outperformed Dressilk ® by providing higher wound transparency rates and offering a better level of wound control during the entire study period. Regarding their cost efficiency, PolyMem ® and Dressilk ® are clearly superior to Biobrane ® . Conclusion: The "ideal" wound dressing maximizes patients' comfort while reducing pain and the risk of pulling off migrating epidermal cells from the wound surface. In addition reliable wound status evaluation (minimizing complications), an increase of treatment cost value efficacy, and reduced hospitalization rates should be provided. Dressilk ® and Biobrane ® were favored by patients and surgeons for providing an effective and safe healing environment, with overall low complication rates with respect to infection and exudation. Regarding cost-effectiveness PolyMem ® and Dressilk ® presented superior to Biobrane ® .